Constructing Multi-Religious Identity A Narrative Self Approach - Cho, Eunil David (2018)
In recent years, a number of pastoral theologians have explored the common reality of "multi-religious belongings." Among those doing these studies are Duane Bidwell (2008, 2015), Emmanuel Lartey (2013), Insook Lee (2011), and Hee-Kyu Heidi Park (2012). By building upon Bidwell's constructivist approach to understanding multi-religious identity, I present a narrative approach as a way to illustrate how that identity is constructed. I will turn to Elizabeth Kim's memoir, Ten Thousand Sorrows, in which she reveals how she has navigated her life as a biracial adoptee. Her narrative is a poignant demonstration of how one's multi-religious belonging is socially constructed and performed, particularly within the context of the USA.
Keywords: Adoption; Buddhism; Korean-American; biculturalism; Interfaith Dialogue; multi-religious identity; narrative self; social constructivism